IMPLEMENTASI PEMBELAJARAN MENGENAL MACAM-MACAM ALAT MUSIK DENGAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA FLIPBOOK - Nurul Hidayah; Eka Titi Andaryani; Udi Utomo; Tri Joko Raharjo; Wadiyo Wadiyo (STKIP Subang, 2024)
Based on observations in Class 5C SD Labschool UNNES, researchers found several problems, namely the lack of understanding of students in recognizing various musical instruments, the lack of active participation of students in learning music, and the learning methods used by teachers are less communicative. This study aims to describe the application of learning to recognize various kinds of musical instruments with the PjBL model assisted by Flipbook Media in learning Music Art in grade V Elementary School. The focus of this research is: (1) Knowing the Kinds of Musical Instruments (2) Steps of the PjBL learning model (3) Flipbook. The approach in this research is qualitative research, while the object of research is Music Learning The subjects of this research are: (1) learning activities to recognize various kinds of musical instruments using the PjBL model assisted by Flipbook. (2) class V C students. (3) Class V C teachers. The method used in this research is descriptive method. Data collection techniques are observation techniques, LKPD work, and making projects by students. Data processing was carried out using qualitative descriptive analysis. The results showed that students' learning understanding in recognizing various musical instruments using the PjBL learning model assisted by Flipbook increased. Based on these results, the use of the PjBL learning model assisted by Flipbook has an effect on understanding the kinds of musical instruments of grade V elementary school students.